A new occupation: A novel & a new occupation: an exegesis on writing a postcolonial travel narrative in the picaresque mode - Kugler, Kerstin Maria (Curtin University, 2013)
A New Occupation investigates the writing of a postcolonial travel narrative in the picaresque mode through a creative piece and an exegetical component. The creative piece is a novel inspired by the colonial travel narrative Fire and Sword in the Sudan, by Rudolf Slatin, and attempts to re-tell it from a postcolonial perspective. The exegesis gives an overview of post-colonial studies of travel narratives and picaresque narrative techniques through a close reading of T.C. Boyle’s Water Music.